Impact of E-Service Quality, Brand Awareness, Advertising, and Brand Image for Repurchase Intention on The Specialty Store - Hendra Bagja Suherman; Mawarti, Janna; Yusuf Iskandar; Pantri Heriyati (Open Access Indonesia Journal of Social Sciences, 2021)
This study aims to examine the effect of e-service quality, brand awareness, advertising in influencing the brand image of the specialty store on the behavior of consumers' decisions to repurchase specialty store products. The sample of this study was taken from the consumer population in the Greater Jakarta area. This study uses a questionnaire to measure the effect of the relationship between independent variables (e-service quality, brand awareness, advertising), and mediating variable (brand image) on the dependent variable (repurchase intention). The research results were analyzed using Partial Least Square (PLS) tools. Based on the results of the study, it was found that e-service quality and brand awareness had a significant effect on brand image, while advertising did not have a significant effect on brand image. For the brand image itself has a significant influence on repurchase intention. The results show that the level of e-service quality and brand awareness plays an important role in improving the brand image in specialty stores. Therefore, to increase the achievement of sales targets, a specialty store needs to improve its brand image because it has an impact on consumer repurchase decision behavior. In this study, the variable e-service quality is used which is a digital-based service through the internet network where previous studies have tested service quality on brand image, but have not focused on digital-based services.